2000
DOI: 10.1038/sj.mp.4000783
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Reelin immunoreactivity in hippocampus of subjects with schizophrenia, bipolar disorder and major depression

Abstract: Accumulation of neurobiological knowledge points to neurodevelopmental origins for certain psychotic and mood disorders. Recent landmark postmortem reports implicate Reelin, a secretory glycoprotein responsible for normal lamination of brain, in the pathology of schizophrenia and bipolar disorders. We employed quantitative immunocytochemistry to measure levels of Reelin protein in various compartments of hippocampal formation in subjects diagnosed with schizophrenia, bipolar disorder and major depression compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
238
0
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 393 publications
(262 citation statements)
references
References 32 publications
19
238
0
5
Order By: Relevance
“…The same group reported reduced reelin levels in cerebellar tissue from five individuals with autism relative to levels in controls [Fatemi et al, 2001b]. This latter finding may not be specific to autism as reduced reelin protein levels have also been reported in cerebellar and other brain regions in schizophrenia, bipolar disorder, and major depression [Impagnatiello et al, 1998;Fatemi et al, 2000Fatemi et al, , 2001aGuidotti et al, 2000]. Finally, in humans, null mutations in RELN cause an autosomal recessive form of lissencephaly, a severe brain developmental disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The same group reported reduced reelin levels in cerebellar tissue from five individuals with autism relative to levels in controls [Fatemi et al, 2001b]. This latter finding may not be specific to autism as reduced reelin protein levels have also been reported in cerebellar and other brain regions in schizophrenia, bipolar disorder, and major depression [Impagnatiello et al, 1998;Fatemi et al, 2000Fatemi et al, , 2001aGuidotti et al, 2000]. Finally, in humans, null mutations in RELN cause an autosomal recessive form of lissencephaly, a severe brain developmental disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in Reelin was associated with significant decreases in Glutamic acid decarboxylase 67 kDa protein, in the same postmortem brains. 59 A later immunocytochemical report, 52 showed significant reductions in Reelin immunoreactivity in schizophrenic and bipolar patients. However, these authors detected similar decreases in hippocampal Reelin protein levels in non-psychotic bipolar and depressed subjects, suggesting that Reelin deficiency may not be limited to subjects with psychosis alone.…”
mentioning
confidence: 96%
“…However, these authors detected similar decreases in hippocampal Reelin protein levels in non-psychotic bipolar and depressed subjects, suggesting that Reelin deficiency may not be limited to subjects with psychosis alone. 52 Fatemi et al subsequently demonstrated significant reductions in Reelin as well as GAD65 and 67 kDa proteins in cerebella of subjects with schizophrenia, bipolar disorder and major depression. 60 Further confirmatory data relating to Reelin abnormalities, in brains of schizophrenic patients, were demonstrated by Eastwood et al, 61 who showed a trend for reduction in Reelin mRNA in cerebella of schizophrenic subjects; these reductions in Reelin mRNA correlated negatively with semaphorin 3A.…”
mentioning
confidence: 99%
See 2 more Smart Citations